Knee Biomechanics During Neurocognitively Challenged Drop Landings in Male Elite Soccer Players with Anterior Cruciate Ligament Reconstruction - Ghazal Mohammad Gholipour Aghdam; Mohammad Hossein Alizadeh; Hooman Minoonejad; Elham Shirzad; Jan Wilke (SpringerOpen, 2024)
Abstract Background Reactive decision-making during athletic movement has been demonstrated to evoke unfavorable biomechanics associated with anterior cruciate ligament (ACL) rupture. However, the current evidence is based on assessments of healthy individuals. We aimed to investigate unplanned jump landing kinetics and knee kinematics in ACL-reconstructed (ACLR) and non-injured athletes. Methods A total of 30 male professional soccer players (n = 15 ACLR after return to play, n = 15 matched controls) performed six drop landings onto a force plate. As a neurocognitive challenge requiring decision-making, a diode flashing in randomly selected colors indicated the requested landing location. Knee joint kinematics (flexion, valgus and tibial rotation angles) assessed with a 10-camera motion capture system, vertical ground reaction force (vGRF), time to stabilization (TTS) and length of the center of pressure (COP) trace (all analyzed from force plate data) were calculated. Cognitive function was assessed using the CNS Vital Signs battery. Results The ACLR group produced lower knee flexion angles than the control group (median [interquartile range] 50.00° [6.60] vs. 55.20° [4.45], p = .02). In addition, path length of the center of pressure (379 mm [56.20] vs. 344 mm [37.00], p = .04) and ground reaction force (3.21 N/kg [0.66] vs. 2.87 N/kg [0.48], p = .01) were higher for the ACLR group. No differences were found for knee valgus (p = .96), tibial rotation (p = .83) and TTS (p = .82). ACLR participants scored lower for reaction time (p = .02) and processing speed (p = .01). Unfavorable knee biomechanics were more often related to cognitive function in the ACLR group than in the control group (p < .05). Conclusions Impaired reactive decision-making during athletic movement may contribute to the high re-injury risk in individuals with ACLR. Prospective studies confirming potential cause-effect relationships are warranted.